Fully integrated CMOS overvoltage protection circuit for automotive applications. Issue 17 (1st August 2015) - Boni, A.; Tonelli, M.; Magnanini, A.; Caselli, M.
Abstract : The voltage signal at the output of the power device driving the ignition coil or the fuel injector of a car engine is often required to be detected and processed for control and diagnostic purposes. Providing this kind of signals to an integrated circuit raises several design and reliability issues due to the presence of voltage peaks of several hundred volts. The design and implementation of an integrated detection and overvoltage protection circuit is presented. A prototype chip was implemented in a 350 nm CMOS technology without a thick‐oxide option. The measured performance over the −40 to +125°C temperature range is in good agreement with the simulation results.